THE ECOLOGICAL AND MELIORATIVE CHANGES IN THE SOIL OF SUKH CONE SPREAD (Scientific journal of the Fergana State University, 2023)
In article describes properties of irrigated soils of the Sukh river cone, ecosystem-reclamation state and classification of soils, agrochemical properties of soils developing on the territory. The mechanical composition of soils, genetic basis and systematic condition of soils are shown.